GERAKAN AKSI BELA ISLAM - Tri Handayani (Al-Dirayah, 2020)
Aksi Bela Islam or Act of Islamic Defense is a series of rallies in Indonesia and other countries often triggered by expressions or attitudes that show displeasure and contempt for Islam. The actions occurred as the public's response to the government being slow to deal with and process perpetrators of "humiliation." From street actions to boycott, sometimes happen to counter distaste for insults. This work aims to look at a similar track record in the past, in the dawn of Islam, and to find out the act's position.